EURÓPA ÚJ GENERÁCIÓS PÉNZFORGALMI RENDSZEREI - Taczmann, Róbert (Közép-Európai Közlemények, 2019)
ABSTRACT In the 2300 year history of money we never experienced such a quick and powerful transformation in the function and the forms of appearance of money. This process started a few decades ago, after technology developments enabled the use of electronic forms of money and made possible new services using that form. Technology alone could not have been able to change everyday use of money, luckily it met the market needs that resulted in significant changes and led all of us to be able to simplify our life and the way we use money. However there are several applications and use cases, one of the most interesting is Instant Payments Systems. These implementations exist in more than 42 countries Today coming along with more than 10 planned systems. Geographically IPS’s are diverse, implementations can be found in North and South America, Europe, Asia Pacific region as well as in Africa. This paper explores the root causes of their importance and popularity with an outlook to the World and European implementations. The paper also discusses their contribution to the national eco-systems, showing the most important benefits of IPS on both customer and economy level. We also see the lessons learnt from the implementations already have gone live in Europe and review the expectations towards the new Instant Payments Systems of the European Union, TIPS. Expectedly, the rapid development of IPS around the World will lead to the forming the Internet of Payments, a global network of interconnected financial services that can be accessed by anybody from anywhere.